2013
DOI: 10.1038/ncomms3939
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold function of long non-coding RNA HOTAIR in protein ubiquitination

Abstract: Although mammalian long non-coding (lnc)RNAs are best known for modulating transcription, their post-transcriptional influence on mRNA splicing, stability and translation is emerging. Here we report a post-translational function for the lncRNA HOTAIR as an inducer of ubiquitin-mediated proteolysis. HOTAIR associates with E3 ubiquitin ligases bearing RNA-binding domains, Dzip3 and Mex3b, as well as with their respective ubiquitination substrates, Ataxin-1 and Snurportin-1. In this manner, HOTAIR facilitates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
360
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 400 publications
(369 citation statements)
references
References 38 publications
7
360
0
2
Order By: Relevance
“…It has recently been reported that the lncRNA HOX transcript antisense RNA (HOTAIR) functions as a scaffold that enhances E3-mediated ubiquitination and degradation of substrate proteins (38). It has also been shown that lincRNA-p21, originally identified as a p53-inducible lncRNA that mediates p53-induced apoptosis in mouse cells (39), is a hypoxia-responsive lncRNA that plays a critical role in the regulation of hypoxia-enhanced glycolysis by inhibiting von Hippel-Lindau (VHL)-mediated hypoxia inducible factor 1 alpha (HIF1α) ubiquitination (40).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that the lncRNA HOX transcript antisense RNA (HOTAIR) functions as a scaffold that enhances E3-mediated ubiquitination and degradation of substrate proteins (38). It has also been shown that lincRNA-p21, originally identified as a p53-inducible lncRNA that mediates p53-induced apoptosis in mouse cells (39), is a hypoxia-responsive lncRNA that plays a critical role in the regulation of hypoxia-enhanced glycolysis by inhibiting von Hippel-Lindau (VHL)-mediated hypoxia inducible factor 1 alpha (HIF1α) ubiquitination (40).…”
Section: Discussionmentioning
confidence: 99%
“…Some lncRNPs can affect gene expression at the transcriptional level; for example, lncRNA ANRIL represses p16INK4 transcription by interacting with the PRC2 complex at the INK4 locus, 24 and lncRNA GAS5 binds glucocorticoid receptors (GCRs) and thus acts as a decoy to prevent the transcriptional activity of GCRs. 25 Other lncRNPs can affect gene expression post-transcriptionally, 26 including the DNA damage-inducible lncRNA gadd7, which associates with the RBP TDP-43 and interferes with the ability of TDP-43 to stabilize CDK6 mRNA, 27 and LincRNA-RoR, which interacts with the RBP HNRNPI, an enhancer of TP53 production, and thus represses TP53 translation. 28 Similar to these examples, HuR-circRNA complexes (HuR circRNPs) may also influence the function of HuR by altering its ability to bind other target RNAs.…”
mentioning
confidence: 99%
“…This shows that the idea that Trim25 is using the RNA as a scaffold to get close to and modify RNP complexes might not limited to Trim proteins. This was also demonstrated by the E3 ligases Dzip3 and Mex3b which bind the long non-coding RNA HOTAIR, which acts as an RNA scaffold bringing them closer to their respective substrates, Ataxin-1 and Snurportin-1, leading to their ubiquitination [50].…”
Section: Trim25 Is An Rna-binding Proteinmentioning
confidence: 99%